A Novel Four-Component Reaction Between a Secondary Amine and Salicylaldehyde with Isocyanide in Water - Gharakhani, F.; Vessally, E.; Mohammadi, A.; Alimadadi, Z. (Asian Journal of Chemistry, 2013)
Reaction of isocyanide with iminium ion intermediate, formed by reaction between an electron deficit salicylaldehyde and a secondary amine in the presence of water proceeds smoothly at room temperature to afford benzo[b]furan derivatives (7) in high yields.